Mengembangkan Kecerdasan Majemuk Siswa Sekolah Dasar (SD) Melalui Pembelajaran IPA Untuk Meningkatkan Mutu Lulusan Sekolah Dasar - I Komang Wisnu Budi Wijaya (Jurnal Penjaminan Mutu, 2018)
The progress of a nation is determined by the quality of Human Resources (HR). One characteristic of qualified human resources is to have multiple intelligences. Multiple intelligences consisting of linguistic, logical-reasoning, bodily kinesthetic, interpersonal, intrapersonal, musical, naturalist, and spatial. Development of multiple intelligences can be done since primary school, one of which is using science learning. The characteristics of the science learning process can allows the growth of multiple intelligences in primary school students.The development of multiple intelligences in primary schools requires important roles of teachers and schools. Multiple intelligences will help students to achieve the specified competency standards.